Penggunaan Solfegio pada Ekstrakurikuler Drumband di SMP Negeri 8 Padang - Eko Hadi Prasetyo; Jagar Lumban Toruan; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2015)
Abstrak The purpose of this research was to describe the use of solfegio in drum band extracurricular activities at SMP N 8 Padang. The activities covered praticing rhythm and melody through audio-visual. This was a qualitative research which applied descriptive analysis method. The object of the research was the use of solfegio in drum band extracurricular activities at SMP N 8 Padang. The date were collected through observation, documentation, and library study. The result of the research revealed that, after the students were trained to listen to the rhythm and melody (audio) and read the rhythm and melody (visual): (1) the students’ knowledge and concept about music increased, (2) the students’ ability to read rhythm notation and melody increased, (3) the students’ skill to use rhythm notation and melody on musical instrument they could play increased, (4) the student’ skill to play music together in presenting the song got better, and (5) the students’ were more excited and self-confident to take part in drum band extracurricular activities. Keyword: Use, Solfegio, Drum band